The Next Voting Debacle?. - Cherry, S.
New provisions in the Help America Vote Act (HAVA) of 2002 have quietly created the potential to disrupt the US elections in November 2006. A major concern are the new HAVA rules that deal with the databases that contain the voter rolls. With these rules, voter eligibility will depend in large part on the contents of a number of databases, most of which have been existence for less than a year and some of which have not been constructed in accord with the best practices of the database industry. While they appear sound, these rules give the states wide latitude in reacting to database mismatches. Many are concerned that this could lead to voter disenfranchisement with tens of thousands of people being disqualified
Keywords: HAVA; Help America Vote Act; Social Security Administration; US elections; Database mismatches; Voter disenfranchisement; Voter disqualification; Voter eligibility; Voter rolls databases